Step-by-step explanation:
(g - f) means that we have to subtract f(t) from g(t)
(g - f)(t/2) means that to the resulting function from the previous operation we have to replace each t by t/2:
Let's do the first part:
![\begin{gathered} g(t)-f(t)=(4t+4)-(t^2+2t) \\ g(t)-f(t)=4t+4-t^2-2t \\ g(t)-f(t)=-t^2+(4t-2t)+4 \\ g(t)-f(t)=-t^2+2t+4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5prxl07y0q4j7jf22q3sf47rxdnyllwj6h.png)
Now we have to replace t by t/2:
![(g-f)((t)/(2))=-((t)/(2))^2+2((t)/(2))+4](https://img.qammunity.org/2023/formulas/mathematics/college/8nbghto8zv4iuaocrytoszq7s9f6o6bano.png)
And we can simplify some fractions:
![\begin{gathered} (g-f)((t)/(2))=-(t)/(4)^2+(2t)/(2)+4 \\ (g-f)((t)/(2))=-(1)/(4)t^2^{}+t+4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kqky94z6drtx6dso0vgd9059rn1fpkjrk6.png)
Answer:
![(g-f)((t)/(2))=-(1)/(4)t^2+t+4](https://img.qammunity.org/2023/formulas/mathematics/college/s2o0ykexxrth5x4cw70lp5v6igivymbhoh.png)